A COMPANY’S CARBON FOOTPRINT AND SUSTAINABLE DEVELOPMENT - Gramc, Jure; Stropnik, Rok; Mori, Mitja (Journal of Energy Technology, 2023)
Climate changes are already here. And they will get much worse in time. The main reason for global warming is GHG emissions from anthropological sources. That includes transportation, industry, electricity production, agriculture, and others. The European Union has introduced a new Green Deal as an answer to climate change. The European Green Deal puts more pressure on companies to mitigate their carbon footprint and implement sustainable development. One of the basic steps in the analysis of the environmental profile of a company is the identification of hot spots by using the carbon footprint methodology. The workflow of the carbon footprint calculation follows GHG Protocol standardised methodology. The calculation was made for a medium-sized company in the plastics industry. For all GHG emission sources, hot spots were identified and analysed. Based on the hot spots, sensitivity analysis for different pre-defined scenarios has been made, which are aligned with the company’s mid- and long-term sustainability goals. The three main hot spots of the company within scopes 1 and 2 are purchased heat, purchased electricity, and combustion of fuels in company vehicles. GHG emissions of heat and electricity are dependent on their distributor and their electricity and heat sources. The hot spot of scope 3 is purchased goods, especially plastic granulate. In the study, we focus only on scope 1 and scope 2.